Isolation of type-specific polysaccharide antigen from group B type Ib streptococci (The Rockefeller University Press, 1979)
Group B streptococcus type Ib (strain H36B) was subjected to digestion with extracellular muralytic enzymes prepared from Streptomyces albus. Type Ib-specific polysaccharide antigen was isolated from the lysate by alcohol precipitation and Sepharose 6B chromatography. The purified type Ib antigen has a Kd value of 0.31 on a Sepharose 4B column and contains four sugars, galactose, glucose, N-acetyl glucosamine, and sialic acid in a molar ratio of 2.05:0.86:1.00:0.90. Acid treatment (pH 2.0) of this polysaccharide results in partial degradation of the antigen (Kd = 0.41 on Sepharose 4B) with the loss of 93% of the sialic acid. The molar ratio of the remaining sugars in the polysaccharide remains identical to that in the native one. This suggests that the sialic acid is at the terminal position in the molecule. Both intact and acid-treated antigen cross-react with some type Ia and type Ic antisera as a result of the common Iabc determinant, but not with type II and type III antisera. Absorption studies indicate that Ib-specific determinant and Iabc determinant are on the same molecule and that sialic acid is not the cross-reactive determinant.